MATRIX OF ROSSIJUVANNYA ATENUATOR WITH ELECTRONIC KERUVANIAM - Ilnytsky , L. Ya.; Shcherbina , O. A. (Problems of Informatization and Control, 2021)
The derivation of the scattering matrix of an electronically controlled attenuator based on the section of the attenuator block diagram on a set of multipoles is considered.